Capillary imbibition depth in particle-bed 3D printing – Physical frame and one-dimensional experiments. (June 2022) - Zuo, Wenqiang; Dong, Chenghao; Belin, Patrick; Roussel, Nicolas; Keita, Emmanuel
Abstract: This paper deals with the control of the net geometry of a printed object in the case of powder-bed or particle bed binding technologies. We first measure and compare water penetration in one-dimensional experiments for various powder-beds. Our results, despite the simplicity of the experimental set-up, show a feature that has not been reported in literature so far, namely the fact that water penetration depth is not finite but is fully uncontrolled on longer time scales. We discuss the physical origin of this feature and the reasons why it is hidden by other aspects in most papers or applications. We finally show that water penetration depth can be controlled by a dispersed organic water thickener. Our results suggest the formation of a non-Newtonian fluid between the binder grains, which allows, in turn, for the control of the naturally uncontrolled capillary-driven water penetration in the powder-bed.